The effects of reaction conditions on the production of Î³-cyclodextrin from tapioca starch by using a novel recombinant engineered CGTase - Goh, Kian Mau; Mahadi, Nor Muhammad; Hassan, Osman; Abdul Rahman, Raja Noor Zaliha Raja; Illias, Rosli Md (Elsevier B.V., 2007)

(untitled)
A novel mutant enzyme namely H43T CGTase can produce up to 39% Î³-cyclodextrin (Î³-CD) compared to the native enzyme which produces only 10% Î³-CD. The effect of the reaction conditions on Î³-CD production was studied using this mutant CGTase. The effects of substrate-buffer combination, starch pretreatment and concentration, pH, additives and finally the use of a debranching enzyme improved the Î³-CD ratio further. The tapioca-acetate pair gave the highest conversion (16% conversion) among four types of starch and four buffer system combinations. Gelatinized starch was preferred compared to raw tapioca starch in producing a high percentage of Î³-CD and conversion rate. Higher pH especially pH 8-9 led to a higher proportion of Î³-CD, and was relatively more apparent when the concentration of starch was increased. Forty-six percent Î³-CD was produced using 2.5% gelatinized tapioca starch at pH 8. Pullulanase enzyme was found to be useful in reducing the viscosity of tapioca starch paste thus increasing the efficiency of utilization of starch by CGTase by at least 20- to 30-fold. Up to 48% Î³-CD can be produced when 4% pullulanase-pretreated tapioca starch was reacted with the CGTase mutant. It was also found that the supplementation of the reaction mixture with glucose, toluene, or cyclododecanone improved the Î³-CD yield by 42.2, 46.4, 43.4, and 43.4%, respectively. All the parameters involved have been shown to affect the product specificity of the mutant H43T CGTase transglycosylation mechanism.